Higher fuel and food prices: Economic impacts and responses for Mozambique - Arndt, Channing; Benfica, Rui; Maximiano, Nelson; Nucifora, Antonio M.D.; Thurlow, James (International Food Policy Research Institute, 2008)
Rising world prices for fuel and food represent a negative terms-of-trade shock for Mozambique. The impacts of these price increases are analyzed using various approaches. Detailed price data show that the world price increases are being transmitted to domestic prices. Short-run net benefit ratio analysis indicates that urban households and households in the southern region of the country are more vulnerable to food price increases. Rural households, particularly in the northern and central parts of Mozambique, often benefit because they sell more food goods than they consume (i.e., net seller). Long-term analysis using a computable general equilibrium model of Mozambique indicates that the fuel price shock dominates rising food prices from both macroeconomic and poverty perspectives. Here again, negative impacts are greater in urban areas than in rural areas. The importance of agricultural production response in general, and export response in particular, are highlighted in this discussion. Policy analysis reveals difficult trade-offs between short-run mitigation and long-run growth. Improved agricultural productivity has powerful positive impacts, but remains difficult to achieve and may not address the immediate impacts of higher prices.